Kiai dan Konflik Elite Politik Lokal di Banyuwangi: Kiai and Local Political Elite Conflict in Banyuwangi - Ali Maksum (Fenomena, 2017)
The direct election of regional heads in Banyuwangi triggered a prolonged political conflict involving not only political elites but also religious leaders (kiai) and the public. This study aims to analyze the patterns of local political elite conflict and the failure of conflict resolution mechanisms during the 2005 Banyuwangi regency election. Using a qualitative case study approach, data were collected through interviews, documentation, and media reports. The findings reveal that the conflict originated from internal splits within the PKB party, worsened by the controversial decision of the Local Election Commission (KPUD), and evolved into religiously charged tensions post-election. Kiai became deeply involved due to allegations of religious blasphemy and policies deemed offensive to Islam. Conflict resolution efforts through interactive dialogue, mediation, and legal approaches failed due to mutual distrust and non-compliance with court decisions. The study concludes that political immaturity among local elites and the absence of good-faith negotiations prolonged the conflict, recommending the strengthening of inclusive mediation frameworks and political education for religious and community leaders. Pilkada langsung di Banyuwangi memicu konflik politik berkepanjangan yang melibatkan tidak hanya elite politik tetapi juga kiai dan masyarakat luas. Penelitian ini bertujuan menganalisis pola konflik elite politik lokal dan kegagalan mekanisme penyelesaian konflik dalam Pilkada Banyuwangi 2005. Dengan pendekatan kualitatif studi kasus, data dikumpulkan melalui wawancara, dokumentasi, dan pemberitaan media. Temuan penelitian menunjukkan bahwa konflik bermula dari dualisme internal PKB, diperparah oleh keputusan kontroversial KPUD, dan berkembang menjadi konflik bernuansa agama pasca-pilkada. Kiai terlibat intensif karena dugaan pelecehan agama dan kebijakan bupati yang dianggap menyinggung Islam. Upaya penyelesaian melalui dialog interaktif, mediasi, dan pendekatan legalistik gagal karena rasa saling curiga dan ketidaktaatan terhadap putusan pengadilan. Kesimpulannya, ketidakdewasaan politik elite lokal dan tidak adanya itikad baik dalam negosiasi memperpanjang konflik, sehingga direkomendasikan penguatan mediasi inklusif dan pendidikan politik bagi tokoh agama dan masyarakat.